Corneal topography, an overview of its devices and systems - A review - Al-Sharify N.T.; Ahmed S.M.; Nser H.Y.; See O.H.; Al-Sharify Z.T.; Ghaeb N.H.; Weng L.Y. (American Institute of Physics Inc., 2024)
With advancements in technology, it is now possible to explore the characteristics of a cornea in depth. A computer-aided diagnostic tool known as corneal topography can create a 3D map of the cornea and its surface curvature. The cornea contributes around 70% of the focusing power of an eye. It is known that evenly rounded corneas are found in eyes with normal vision. However, in cases where the eye cornea is either unevenly curved, is too steep or is too flat, it may result in vision issues. Corneal topography is a non-invasive, experimental method for assessing the cornea's morphology in qualitative and quantitative terms. Corneal topography is a visual representation of the structure and strength of the cornea. The technique can measure anterior and posterior corneal layers in three dimensions. In this research review, a review of the devices used to examine the cornea will be presented, what is extracted from each device, the working theories of each device, the general specifications extracted from the results and the outputs of each device 2023 Author(s).